Innovative financing mechanisms for climate adaptation in African agrifood systems - D’Alessandro, Cecilia; Adeniyi, Daniel; Araba, Lade (AKADEMIYA2063, 2024)
Agrifood systems are a leading cause of climate change globally, as they are responsible for a third of anthropogenic greenhouse gas (GHG) emissions, the majority of which are tied to agricultural production (39 percent), followed by land use (32 percent) and supply chain activities (29 percent). Moreover, unsustainable agricultural practices continue to drive 80 percent of the loss of terrestrial biodiversity, soil degradation, and deforestation and are responsible for 70 percent of global freshwater withdrawals. GHG emissions are projected to increase by 60 to 90 percent through 2050 unless corrective action is taken (Apampa et al. 2021). Africa’s share of global GHG emissions is small (2 to 3 percent) but rising, with agriculture and land use change as major contributors (Adolph, Griffiths, and Hou-Jones 2023; FAO 2022).